Influence of fungicide and sowing density on the growth and yield of two groundnut cultivars - Naab, J.B.; Boote, K.J.; Prasad, P. V. Vara; Seini, S.S.; Jones, J.W. (My University, 2011)
Groundnut or peanut (Arachis hypogaea L.) is a valuable food and forage crop in West Africa. It is important to determine yield-limiting factors and to develop suitable management practices to improve groundnut productivity. The objective of the present research was to determine the influence of fungicide application at different sowing densities on growth, biomass and yield of early and late maturing groundnut under rainfed conditions. Two groundnut cultivars (Chinese, 90 days duration and Manipinter, 120 days duration) were grown at low (8 plants/m2), medium (12 plants/m2) and high density (20 plants/m2), with and without fungicide application, for two growing seasons (2004 and 2005). Data on leaf area index (LAI), light interception (LI) and total biomass were measured at different stages of crop development. Haulm (stem and leaf), pod and seed yields were measured at maturity. Fungicide application increased LAI, LI and total biomass of both cultivars from 65 days after sowing (DAS) until maturity. Fungicide application significantly increased pod and seed yields by 95 and 103%, respectively, on average. In both years, the long duration cultivar Manipinter had significantly greater LAI, LI and total biomass at later stages of crop development when compared with the short-duration cultivar Chinese. The growth and yield of both cultivars were significantly less at the lowest population density when compared with medium or high population densities. There was no significant difference between medium and high population densities in haulm, pod and seed yield at maturity. It is concluded that sowing a long-duration cultivar at a density of 12 plants/m2 with fungicide application significantly improved groundnut yields under rainfed conditions in Ghana.
Citation: Naab, J. B., K. J. Boote, P. V. V. Prasad, S. S. Seini, and J. W. Jones. “Influence of Fungicide and Sowing Density on the Growth and Yield of Two Groundnut Cultivars.” The Journal of Agricultural Science 147, no. 2 (April 2009): 179–91. https://doi.org/10.1017/S0021859608008290.
Keywords: Arachis hypogaea L; Fungicide application; Groundnut; Sowing density; Ghana